A combined model of electron density and lattice dynamics refined against elastic diffraction data. Thermodynamic properties of crystalline l‐alanine. Issue 1 (18th December 2019) - Sovago, Ioana; Hoser, Anna A.; Madsen, Anders Ø.
Abstract : A combined refinement of a lattice‐dynamics and electron‐density model is introduced. Abstract : Thermodynamic stability is an essential property of crystalline materials, and its accurate calculation requires a reliable description of the thermal motion – phonons – in the crystal. Such information can be obtained from periodic density functional theory (DFT) calculations, but these are costly and in some cases insufficiently accurate for molecular crystals. This deficiency is addressed here by refining a lattice‐dynamics model, derived from DFT calculations, against accurate high‐resolution X‐ray diffraction data. For the first time, a normal‐mode refinement is combined with the refinement of aspherical atomic form factors, allowing a comprehensive description and physically meaningful deconvolution of thermal motion and static charge density in the crystal. The small and well diffracting l ‐alanine system was used. Different lattice‐dynamics models, with or without phonon dispersion, and derived from different levels of theory, were tested, and models using spherical and aspherical form factors were compared. The refinements indicate that the vibrational information content in the 23 K data is too small to study lattice dynamics, whereas the 123 K data appear to hold information on the acoustic and lowest‐frequency optical phonons. These normal‐mode models show slightly larger refinement residuals than their counterparts using atomic displacement parameters, and these features are not removed by considering phonon dispersion in the model. The models refined against the 123 K data, regardless of their sophistication, give calculated heat capacities for l ‐alanine within less than 1 cal mol −1  K −1 of the calorimetric measurements, in the temperature range 10–300 K. The findings show that the normal‐mode refinement method can be combined with an elaborate description of the electron density. It appears to be a promising technique for free‐energy determination for crystalline materials at the expense of performing a single‐crystal elastic X‐ray diffraction determination combined with periodic DFT calculations.